2022
DOI: 10.1002/jmv.28358
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐minimization analysis of DTaP‐IPV‐Hib combination vaccine in China: A nationwide cross‐sectional study

Abstract: Combination vaccines can reduce the vaccination visit, simplify the vaccination schedule and efficiently improve management. This study was primarily designed to evaluate the economic impact of integrating the diphtheria‐tetanus‐acellular pertussis inactivated poliomyelitis and Haemophilus influenzae type B (DTaP‐IPV‐Hib) combination vaccine into the China National Immunization Program. A cost‐minimization analysis (CMA) compared the costs associated with direct medical, direct nonmedical, and indirect social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…People in high-income region may weigh the pros and cons of vaccine safety and efficacy more because of high educational attainment and improved vaccine knowledge [ 35 ]. And the time and effort cost of vaccination for high-income parents is often higher than that for low-income parents, further increasing the precepted barrier [ 36 ]. Moreover, those in middle-to-high-income areas may have easier access to information through the internet and social media, which may lead to increased exposure to anti-vaccine information.…”
Section: Discussionmentioning
confidence: 99%
“…People in high-income region may weigh the pros and cons of vaccine safety and efficacy more because of high educational attainment and improved vaccine knowledge [ 35 ]. And the time and effort cost of vaccination for high-income parents is often higher than that for low-income parents, further increasing the precepted barrier [ 36 ]. Moreover, those in middle-to-high-income areas may have easier access to information through the internet and social media, which may lead to increased exposure to anti-vaccine information.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that multi-component vaccines have seen significant increases in usage nationwide, avoiding the pain caused by multiple injections of component vaccines, reducing physical and human resources costs, and lowering expenses. This approach also reduces visits to vaccination clinics to avoid the cross-contamination with other intranasal spray vaccines, leading to improved compliance among recipients and increased immunization coverage ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%